KEDEWASAAN DALAM PERUBAHAN UNDANG-UNDANG BATAS USIA PERKAWIANAN - Gusti Muhammad Andre; Mohammad Noviani Ardi (Indonesian Association of Islamic Family Law Lecturers, 2020)
This study aims to determine the age limit for adulthood in carrying out marriage through a psychological perspective based on the amendment of Law No. 1 of 1974 to Law No. 16 of 2019. The benefit of this research is to find out how the ideal adult age limit in carrying out marriage and also know how early marriage impacts. This research method uses a qualitative descriptive analysis approach in which data collection techniques are used through interviews which are then compiled and reported and then drawn logical conclusions. The subjects in this study were several members of the Central Java HIMPSI (Indonesian Psychological Association). The results of this study can be concluded in the form of the ideal age limit in carrying out marriage through the HIMPSI perspective, namely the age of 21-25 years because at that age the prospective bride and groom are mature from the aspects of health, cognitive, emotional, social, educational and economic.